How did blue and green water resource evolute spatially and temporally in the Meijiang River Basin, China? - Liu, Youcun; Yang, Shuyue; Meng, Lihong; Liu, Tao; Zhu, Mingyong; Ou, Xiaolin; Xiong, Yongzhu; Labat, David (Frontiers in Earth Science, 2023)
Water is the source of all life on Earth. Blue water and green water are important for water re-source evaluation and are also essential for the efficient use of water resources. By constructing a SWAT model to simulate the spatial-temporal evolution of blue water and green water resources in the Meijiang River Basin from 2008 to 2018, this paper explored the spatial-temporal distribution characteristics of blue water and green water and evaluated the change trend of the green water coefficient. The results showed that: (1) the average amount of blue water resources per unit area in the Meijiang River Basin was 921 mm, accounting for 43% of the total water resources; the amount of green water resources was 1232 mm, accounting for 57% of the total water resources, resulting in a green water coefficient of 57%. (2) blue water quantity and precipitation were highly positively correlated, and the overall change in green water quantity had been relatively stable. Water quantity of green also showed a positive correlation with precipitation within a certain range, while the green water coefficient and precipitation showed a highly negative correlation; (3) precipitation and other climatic conditions were the decisive factors affecting the amount of blue water resources in the basin, whereas the nature of the underlying surface, such as the vegetation or land use, altitude, and topography, was the main factor affecting the green water volume of the watershed.